2009
DOI: 10.1002/jca.20214
|View full text |Cite
|
Sign up to set email alerts
|

Postdonation platelet counts are safe when collecting platelets with the Trima Accel using a postdonation platelet count target of ≥50,000 platelets/μL

Abstract: In December 2007, the FDA issued a guidance document recommending that apheresis cell separators be configured with a postdonation platelet count target of > or =100,000 platelets/microL. Currently, our Trima Accel apheresis cell separators are configured with a postdonation platelet count target of > or =50,000 platelets/microL. To determine the safety of our current procedure, we analyzed the postdonation platelet counts of 115 donors collected using our current procedure. All of 115 donors had postdonation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In some apheresis systems, for example the Trima Accel 5.1 with the original PLT post prediction used in this study, PLT recruitment was not considered in the algorithm that predicts PLT post , which is based only on the estimated donor blood volume, PLT pre , and the target PLT yield to predict PLT post . A recent study has suggested that such a prediction underestimates the real PLT post 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some apheresis systems, for example the Trima Accel 5.1 with the original PLT post prediction used in this study, PLT recruitment was not considered in the algorithm that predicts PLT post , which is based only on the estimated donor blood volume, PLT pre , and the target PLT yield to predict PLT post . A recent study has suggested that such a prediction underestimates the real PLT post 7 …”
Section: Discussionmentioning
confidence: 99%
“…First, some studies suggested a recruitment of PLT during plateletpheresis, defined as a ratio more than one of the effective and the predicted PLT yield based on donor blood volume and difference between PLT pre and PLT post 5,6 . If PLTs are recruited into the donor blood circulation during apheresis, the effective PLT post will be higher than conservatively predicted, and the limit setting required by the FDA may be applied too restrictively with current algorithms 7 . There are data suggesting that PLTs are indeed recruited from the spleen during apheresis, 8 in particular based on the observation that splenectomized patients in remission from leukemia did not show such a recruitment 6 .…”
mentioning
confidence: 99%